Phosphorus-nitrogen compounds. Part 44. The syntheses of N,N-spiro bridged cyclotriphosphazene derivatives with (4-fluorobenzyl) pendant arms: Structural and stereogenic properties, DNA interactions, antimicrobial and cytotoxic activities - Ozturk, Ezel; Okumus, Aytug; Kilic, Zeynel; Kilic, Adem; Kayalak, Hande; Acik, Leyla; Cerci, Nebahat Aytuna (Elsevier Science Sa, 2019)
Isopropylaminopentachlorocyclotriphosphazene, (N3P3Cl5(NHCHMe2) (1), containing a P-NH group in the alkyl-chain, gives the NN-spirobridged octachlorobiscyclotriphosphazene, [N3P3Cl4(NCHMe2)](2) (2), in the presence of NaH. The reactions of 2 with excess pyrrolidine result in the formation of the fully substituted bridged product 2a. The reactions of 2 with 1:1 and 1:2 equimolar amounts of N-(4-fluorobenzyl)N'methylethane-1,2-diamine and N-(4-fluorobenzyl)-N'methylpropane-1,3-diamine produce the (4-fluorobenzyl) pendant armed monospiro (2b and 2c) and dispiro (2f and 2g) products. These compounds react with excess pyrrolidine to form stable, fully substituted cyclotriphosphazenes (2d, 2e, 2h and 2i). The structures of 2a and 2f are determined by X-ray crystallography. The stereogenic properties of 2a and 2f having four potential stereogenic P-centers are investigated by crystallography. The monospiro (2b-2e) and dispiro (2f-2i) products have one and two equivalent chiral centers, respectively. The dispiro derivatives may have two meso (trans-trans and cis-cis) and two racemate (trans-cis and cis-trans) mixtures. However, the structure of 2f is found to be as trans-trans (meso) isomer. Besides, in vitro antimicrobial and cytotoxic activities of 2d and 2h are evaluated. The compounds exhibit significant growth inhibitory effects on E. coli and B. cereus bacteria. Compound 2d has high anticancer and apoptotic activities.
Keywords: Spiro - bridged phosphazene; Stereoisomer; Crystallography; Antimicrobial activity